(untitled) (Medical Forum Monthly, 2024)
Objective: To investigate the variations in the total number of segmental arteries in human kidneys obtained from cadavers of the local adult population. Study Design: Observational Study. Place and Duration of Study: This study was conducted at Anatomy Department of University of Health Sciences, Lahore, for a period of one year from October 2006 to October 2007. Materials and Methods: Forty four adult human kidneys were obtained after autopsy; they were randomly divided in two groups A and B of right and left kidneys respectively. Simple blunt dissection and corrosion cast techniques were used to study the number of segmental arteries. Statistical analysis was carried out by using SPSS version 16.0 and STATA version 8.0. Results: Segmental arteries were present in 100% of specimens of groups A and B; variations were seen in the number of segmental arteries of both groups. Conclusion: The segmental branches of renal artery in local population showed variations different from those reported in the earlier work carried out in other countries.